In Situ Bone Tissue Engineering With an Endogenous Stem Cell Mobilizer and Osteoinductive Nanofibrous Polymeric Scaffolds. Issue 12 (28th September 2017) - Lee, Jong Seung; Jin, Yoonhee; Park, Hyun‐Ji; Yang, Kisuk; Lee, Min Suk; Yang, Hee Seok; Cho, Seung‐Woo
Abstract : Classical bone tissue engineering involves the use of culture‐expanded cells and scaffolds to produce tissue constructs for transplantation. Despite promising results, clinical adoption of these constructs has been limited due to various drawbacks, including extensive cell expansion steps, low cell survival rate upon transplantation, and the possibility of immuno‐rejection. To bypass the ex vivo cell culture and transplantation process, the regenerative capacity of the host is exploited by mobilizing endogenous stem cells to the site of injury. Systemic injection of substance P (SP) induce mobilization of CD29 + CD105 + CD45 − cells from bone marrow and enhance bone tissue regeneration in a critical‐sized calvarial bone defect model. To provide an appropriate environment for endogenous stem cells to survive and differentiate into osteogenic lineage cells, electrospun nanofibrous polycaprolactone (PCL) scaffolds are functionalized with hydroxyapatite (HA) particles via a polydopamine (PDA) coating to create highly osteoinductive PCL‐PDA‐HA scaffolds that are implanted in defects. The combination of the PCL‐PDA‐HA scaffold and SP treatment enhance in situ bone tissue formation in defects. Thus, this in situ bone regeneration strategy, which combines recruitment of endogenous stem cells from the bone marrow to defective sites and implantation of a highly biocompatible and osteoinductive cell‐free scaffold system, has potential as an effective therapeutic in regenerative medicine. Abstract : Substance P (SP) facilitates tissue regeneration and healing process by mobilizing endogenous stem cells from bone marrow to defective sites. Combination of SP treatment and mussel‐inspired osteoinductive nanofibrous scaffolds significantly enhanced in situ bone regeneration in a critical‐sized bone defect. This strategy can provide a highly effective cell‐free therapy for bone tissue engineering. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB visitwww.afob.org .